PERAN PROGRAM MAGANG DI LPD DESA PAKRAMAN SESETAN DALAM MENINGKATKAN KOMPETENSI MAHASISWA - Ni Luh Putu Yesy Anggreni; Ni Luh Putu Cahayani; Yoseph dreitson garu Yopi; Ni Wayan Ary Rusitayanti (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2026)
Internship programs constitute experiential learning that enables students to connect theoretical knowledge with real workplace practice. This study examines the role of the internship program at LPD Desa Pakraman Sesetan in enhancing student competencies. A descriptive qualitative approach with a case-study design was employed. Data were collected through in-depth interviews, observation, and documentation and were analyzed thematically. The findings show that the internship improved students’ technical competencies in financial administration, service, and data management, while also strengthening soft skills such as communication, teamwork, discipline, and problem-solving. The program further deepened students’ understanding of a customary village-based financial institution. However, its effectiveness was still influenced by students’ initial readiness and the quality of supervision. Therefore, more systematic pre-internship briefing and mentoring are needed to optimize the program’s impact.